"A Fatherland worth living in": Anarchism, citizenship and nation in Bolivia, 1900–1941. Issue 1 (28th October 2022) - Margarucci, Ivanna
Abstract: This paper analyses the particular role played by anarchism in early 20th century discussions concerning the Bolivian nation and citizenship. Based on a diverse corpus of documents and extended specialised literature, I will argue that between the 1920s and 1940s the local anarchist movement took part in these debates by rejecting the Creole oligarchy's definition of the nation and proposing one of its own. Ideologically, this intervention meant imagining a different, more inclusive national community made up of racialised and gendered identities. Practically, it implied fighting against internal colonialism, struggling for equal citizenship, and defending the ethnic and gender identity and human dignity of mestizos, cholas, and indigenous people. By reconstructing these debates and some anarchist "ethno‐classist" struggles of the period, I approach the anticolonial orientation of Bolivian anarchism, and more generally, examine a historical experience in which subaltern subjectivities intervened in nation‐building away from a statist, Western and patriarchal path.